Note: you must isolate the variable you are trying to solve for. Do the opposite to both sides because of the equal sign.
1) solve for y₂
d = y₂ - y₁
Isolate y₂. Subtract y₂ from both sdies
d (-y₂) = y₂ (-y₂) - y₁
d - y₂ = - y₁
Divide -1 from both sides to isolate the y₁
(d - y₂)/-1 = (-y₁)/-1
y₁ = (d - y₂)/-1
2) Solve for b
Isolate the b, subtract c from both sides
a = b + c
a (-c) = b + c (-c)
a - c = b
b = a - c
3) solve for y₁
d = y₂ - y₁
Isolate y₁, subtract y₂ from both sides
d (-y₂) = y₂ (-y₂) - y₁
d - y₂ = - y₁
Divide -1 from both sides.
(d - y₂)/-1 = (-y₁)/-1
y₁ = -d + y₂
hope this helps